Band Spectrum Regressions using Wavelet Analysis - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2011)
In economics it is common to distinguish between different time horizons (i.e. short run, medium run, and long run). Engle (1974) proposed combining the discrete Fourier transform with a band spectrum regression to estimate models that separates between different time horizons. In this paper we discuss possibilities and challenges using the maximal overlap discrete wavelet transform instead of the Fourier transform when estimating band spectrum regressions.
Keywords: C14; C32; C51; 330; band spectrum regression; wavelet transform; frequency domain; economic modeling